2016
DOI: 10.21276/apjhs.2016.3.4.49
|View full text |Cite
|
Sign up to set email alerts
|

Emphatic Tendency and Affecting Factors in Nursing Students

Abstract: Background: The profound impact of empathy on quality nursing care has been recognized. Studies have shown that there has been little improvement in nurses' communication skills, and that they should work to enhance this area. Therefore, it is very important for qualified nursing care to determine empathic tendency and factors that affect in nursing students, so to teach empathic approach and professional values, to develop correct communication and helping skills to the students in nursing education. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[10,18] Similar to the results of the study by Kanbay et al [21] we determined that such variables as age, marital status, the high school graduated, and active participation in social activities did not affect communication skills and emphatic tendency. However, Ister et al [8] found that emphatic tendencies of the students were found to be affected by age, gender, the place of residence, the number of close friends, and the reasons for choosing this profession. Communication style varies by culture and gender [17] The ETS scores differed in terms of gender in both departments (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,18] Similar to the results of the study by Kanbay et al [21] we determined that such variables as age, marital status, the high school graduated, and active participation in social activities did not affect communication skills and emphatic tendency. However, Ister et al [8] found that emphatic tendencies of the students were found to be affected by age, gender, the place of residence, the number of close friends, and the reasons for choosing this profession. Communication style varies by culture and gender [17] The ETS scores differed in terms of gender in both departments (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted by Kanbay et al [21] there was no difference between genders in contrast to this study, while there was a difference in terms of gender in other studies in which female students were found to be more successful. [3,8] It was also determined that students who were satisfied with their profession could communicate more successfully and exhibited more empathic tendency than those who were not. Communication skills and empathy level scores of students who reported having difficulty in daily interactions in our study were found to be as low as the findings of those in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…13 İster and Altınbaş (2016) also found moderate levels of empathic tendencies for nursing students. 27 In the study by Yiğitbaş, Deveci, Açık, Ozan, and Oğuzöncül (2013) that evaluated the empathic tendencies of health education students, ETS mean score of the students was 66.07, ETS mean score of nurses who worked with Özcan (2012) was 65.95, and Avcı, Aydin, and Ozbasaran (2013) stated this mean score as 67.66. [28][29][30] The fact that the cultural sensitivity and empathic tendency of the nurses were at moderate level for nurses makes also us think the necessity of cultural education, as well as the need for increasing the ability for empathy in the trainings to be provided for the students.…”
Section: Scales and Subscalesmentioning
confidence: 99%